Using Thematic Units to Teach EFL in a Venezuelan Context - Marisela B. Serra (Asociación Colombiana de Profesores de Ingles, 2016)
Educators who teach English in Venezuela are faced with many challenges. For example, in the Secondary School Curriculum, English is taught as an academic subject only three hours a week. Although the English syllabus provided by the Ministry of Education is communicatively and functionally based, many teachers still use the techniques suggested by the Audiolingual Approach such as choral repetition, oral drilling, and dialogue memorization. Still, other teachers who learned through the Grammar Translation Method, carry on the tradition of using this method, paying little attention to recent theory and practice.